Juvenile Justice Implementation in Handling Knife-Carrying Offenses within Indonesian Criminal Law - Azzahra Rizki Ananda; Sugeng Dwiono (BRIDGE : The Multidisciplinary Research Portal, 2024)
This study examines the implementation of criminal law in handling juvenile knife-carrying offenses within the Indonesian juvenile justice system, using North Lampung Regency as an empirical case. Adopting a qualitative socio-legal research design, the study analyzes how statutory criminal norms are applied in practice and how their implementation is shaped by institutional, social, and cultural contexts. Primary data were obtained through semi-structured interviews with law enforcement officials, probation officers, and juveniles in conflict with the law, while secondary data consisted of statutory regulations, judicial decisions, and relevant scholarly literature. The findings indicate that juvenile knife-carrying cases are formally processed in accordance with Emergency Law No. 12 of 1951 and juvenile justice regulations, with procedural safeguards for children generally observed. However, the effectiveness of law enforcement is influenced by limited community participation, low legal awareness, and persistent cultural perceptions that normalize the carrying of sharp weapons. These factors contribute to a predominantly reactive enforcement model that emphasizes post-offense handling rather than preventive intervention. The study further reveals a structural tension between the deterrent function of criminal law and the rehabilitative objectives of juvenile justice. This research concludes that juvenile knife-carrying offenses represent an interdisciplinary legal issue that cannot be effectively addressed through doctrinal criminal law alone. A more integrated approach, combining criminal law enforcement, juvenile justice principles, and socio-cultural considerations, is required to achieve sustainable crime prevention and child-centered justice.